PEMERIKSAAN RESIDU ANTIBIOTIK PADA HATI KERBAU DAN IKAN NILA DENGAN METODA DIFUSI AGAR - Musyirna Rahmah NST; Rahayu Utami; Nur Rahmadani Fitri (State Islamic University of Sultan Syarif Kasim Riau, 2010)
This study was aimed to identify antibiotic residue on buffalo liver (Bubalus bubalis) dan nila fish (Oreochromis niioticus). Detection of antibiotic residu was used antibacterial assay by diffusion methode. The result indicated that some of samP/i:.s at concentration 25% contained antibiotic residue with inhibited growth rate Escherichia coli 12,3 nun.